2016
DOI: 10.1007/s11032-016-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure based on EST–SSR: a putative tool for fruit color selection in Japanese plum (Prunus salicina L.) breeding programs

Abstract: Prunus salicina is one of the most economically important stone fruits. However, there is scarce genetic information available, which makes it difficult to implement marker-assisted selection (MAS) in genetic improvement programs. Recently, next-generation sequencing has greatly enhanced breeding program strategies, generating information associated with the identification of expressed sequence tag-simple sequence repeats (EST-SSRs) and single-nucleotide polymorphisms (SNPs), two of the most used molecular mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…A relatively high proportion of hexanucleotide SSRs was also in exons (33%). The nucleotide distribution was approximately equal in the exons (21,24,26, and 28% for T, G, A, and C, respectively), while in NCDS T (46%) and A (34%) prevailed over C (12%) and G (8%). Table 2.…”
Section: Development and Characterization Of Ssr Markersmentioning
confidence: 93%
See 3 more Smart Citations
“…A relatively high proportion of hexanucleotide SSRs was also in exons (33%). The nucleotide distribution was approximately equal in the exons (21,24,26, and 28% for T, G, A, and C, respectively), while in NCDS T (46%) and A (34%) prevailed over C (12%) and G (8%). Table 2.…”
Section: Development and Characterization Of Ssr Markersmentioning
confidence: 93%
“…The SSR markers in the TF gene in plants were first developed by Kujur et al [73], which showed the influence of the SSR polymorphism on secondary structure of proteins and on such traits as seed weight and number of pods and seeds. Since then, there have been few similar studies in Rosaceae where similar markers have been developed for Japanese plum [24], but no such markers have been reported for Rubus and Fragaria before our first study, where we developed a SSR marker representing the RiMYB10 TF gene, an activator of transcription of flavonoid biosynthesis [23]. The association between the MYB10 gene and fruit color has been demonstrated for apple [45] and peach [74].…”
Section: Ssr Markers Representing Transcription Factor (Tf) Genesmentioning
confidence: 98%
See 2 more Smart Citations
“…In Prunus species, single-digest GBS has been used for identification of a high number of SNPs for linkage maps construction [32][33][34][35] and analysis of population genetic structure [36][37][38] . The use of double-digest GBS in Prunus has not been reported as far as the authors know.…”
mentioning
confidence: 99%